Moving Average Investigation in Optimizing Entry and Exit on IDX Sharia Growth - Nurfadillah, Nurfadillah; Haanurat, A Ifayani; Jaya, Asri (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to evaluate the effectiveness of the Moving Average indicator in determining entry and exit times on stocks listed on IDXSHAGROW. This is a reference for sharia stock investors in making investment decisions. This study uses a quantitative approach using the Mann-Whitney test to analyze data from May 2023 to May 2024. The population in this study were companies listed on IDXSHAGROW. The purposive sampling method was used in sampling, as many as 7 companies were consistently listed on the index. Data was obtained through the Profits application. The MAs were compared were MA10 and MA50 with the breakout and breakdown methods to determine signals. The results showed that MA10 produced 154 optimal signals out of 202 signals, while MA50 recorded 52 optimal signals out of 68 signals. Both indicators have the same level of accuracy, which is 76%. However, MA10 is more responsive to price changes. The findings emphasize the importance of understanding analysis for investors in making better investment decisions in the sharia capital market.